High-heat flux tests of tungsten divertor mock-ups with steady-state plasma and e-beam. (December 2020) - Budaev, V.P.; Fedorovich, S.D.; Dedov, A.V.; Karpov, A.V.; Komov, A.T.; Martynenko, Yu.V.; Giniyatulin, R.N.; Makhankov, A.N.; Litunovsky, N.V.; Sliva, A.P.; Marchenkov, A.Yu.; Gerasimov, D.N.; et al.
Highlights: Mock-ups of the ITER tungsten divertor plate were tested with the combination of thermocyclic electron beam tests of up to 40 MW/m 2 and subsequently with steady-state plasma of 0.5–1 MW/m 2 in the PLM plasma device. The tests led to erosion, cracking, and nanostructured "fuzz" growth on the tungsten surface. The "fuzz" layer on tungsten surface was tested with the e-beam. Abstract: Mock-ups of the ITER divertor plate are tested with the combination of steady-state plasma and e-beam loads: (1) thermocyclic tests with powerful electron beam load of up to 49 MW/m 2 in the e-beam facility; and then (2) subsequent testing in the PLM plasma device with steady-state plasma loads of 0.5–1 MW/m 2 and more. Such tests simulate the variable load on divertor plates in the ITER. Tungsten samples are irradiated with helium plasma in experiments on the PLM plasma device with discharge duration of up to 200 min. The tests of ITER-grade tungsten VM-P with the combination of steady-state plasma and thermocyclic e-beam loads led to erosion, cracking, and nanostructured "fuzz" structure growth on the material surface. Post-mortem scanning electron microscopy revealed a stochastic nanostructured surface with dimension of structural elements less than 100 nm. The growth of a nanostructured surface with a "fuzz"-type structure and high porosity is observed. The results of such tests are of interest to estimate the erosion of tungsten in fusion reactors, including ITER, fusion neutron source FNS and DEMO.